O papel do cooperativismo no desenvolvimento do estado do Tocantins - Braúna, Ayrton Alves (Universidade Federal do Tocantins, 2017)
This research started with the following question: Does cooperative business promote the development of the state of Tocantins? As presupposed, it was understoodthat cooperative business acted as a development agent in the state, in view of the various empirical and theoretical evidences related to the role of the cooperative business in the development. From this, it was proposed to analyze the role of cooperative business in the development of the state of Tocantins, in the period of January 1989 and September 2016, in the perception of the main performers of the movement in the state. The specific objectives were: 1) To identify the main events that marked the cooperative business in the State of Tocantins; 2) Identify the contributions of cooperatives to the development of the State of Tocantins; 3) Identify the challenges and potential of cooperative business for the future of the state. It is a qualitative study that is classified as a descriptive-exploratory research, developed through bibliographical research, documentary and semi-structured interviews. In the interviews were used the techniques: snowball and theoretical saturation (at the end were interviewed twelve people). It was used the content analysis technique for data analysis, which happened through three categories of closed grid (Events, Role of Cooperatives in the Development of the State of Tocantins and Cooperatives in the Future). In the results it became evident that the cooperative business of Tocantins is working for the development of the state (in answer to the first question and confirming the presupposed). It can be said that cooperative business promotes the development of the state of Tocantins in various dimensions (social, economic, political and cultural). In short, there are still great challenges for the Cooperatives of Tocantins, although it has been prominent in promoting development in the state, and already has consolidated cooperatives with great capacity to continue promoting the development, with a broad process of social inclusion.